Estrutura da comunidade arbustivo-arbórea e suas interações com o solo em uma área de caatinga, Pombal-PB - HOLANDA, Alan Cauê de (2012)
The Caatinga is one of the only regions in Brazil where its limits are restricted to national territory, and for being the biome fourth in land area in the country, is the most neglected by the political authorities, where there is a strong anthropic disturbance and disorderly exploitation of natural resources, especially for energy, agricultural and pastoral. Given this issue, and the deficiency related to the study of vegetation, is that the present work aims to survey the vegetation in an area of Caatinga, analyze litter production and nutrient; check the rate of decomposition of leaf litterfall of ten species of greatest importance value and quantify the distribution of nutrients in the soil-vegetation. The study was conducted in the remnant forested savanna Riachão Farm located in the municipality of Pombal, PB. For sampling of the adult vegetation were installed 40 plots of 10 m x 25 m in a systematic way, where were inventoried all the individuals with CAP ≥ 10.0 cm. Natural regeneration was evaluated through the implementation of sub-plots of 5 m x 5 m located in the northwestern part of each installment, in which all individuals were sampled with a height H> 1.0 m CNB <10.0 cm. To analyze litter production were installed in the center of each sample unit a collector box with dimensions of 1.0 m2, in which monthly during the period of one year, all material in the boxes were collected and separated by fractions, and 40 plots installed, 16 were selected for realization of analyzes chemistry (N, P, K, Ca and Mg). The decomposition of leaf material was performed for the ten species of highest importance value (VI) recorded in the area in line with the soil respiration. After collecting the leaves, they were distributed in 288 litter bags, and each had a portion of 10.0 g. Samples were collected during one year at intervals of 45 days and then sent to the laboratory for chemical quantification of C and N. To analyze the distribution of nutrients in different compartments of the soilplant system, was collected recent mature leaves from the middle portion of the canopy of ten trees of most important in different orthogonal points, eight soil samples from plots at different depths (0 - 0.1 m, 0.1-0.2 m, 0.2-0.3 m) and portions of organic mantle, all the papers were forwarded to the analyzes chemical. We sampled 1338 individuals in the adult tree shrub component and 365 in natural regeneration. The Shannon diversity index calculated for the adult and regeneration was 1.67 and 1.35 nats individual-1, respectively. Were estimated deposition an annual litter of 3785.67 kg ha-1, the leaf fraction being the largest contributor with 70% and the concentration of nutrients in the litter followed the order Ca>N>K>Mg>P. It was found over a year of the study as a weight loss of 67% and with the soil respiration more intense at night. The C/N rate is relatively low, indicating a higher rate of mineralization. The remaining soil is rich in nutrients and high concentrations of nutrients in the leaves, associated with low concentrations observed in the organic mantle, may be indicative of greater efficiency of the biochemical cycle.